Komunikasi Pembangunan Pariwisata Alam “Back to Nature” Pada Pengembangan Konsep Inovasi “ Glamour Camping” Ciremailand Kuningan Jawa Barat - Wulandari, Ajeng Ayu; Husnita (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2022)
ABSTRACT Currently, tourism activities must pay attention to sustainable tourism development policies, with the concept of